Introduction of Poplar Species in Maharashtra State - an Assessment - Ballal, A. N.; Gogate, M. G.; Dakshindas, S. D.; Karunakaran, M. (Indian Forester, 2001)
Poplars were first introduced in Maharashtra in the year 1979-1980 in Western Ghat Plateau zone. However, this maiden effort met with very limited success due to the incorrect methods of planting. Renewed efforts were made to reintroduce poplars in the sub-mountain zone i.e., Eastern aspect of Western Ghats (rain-shadow zone) during 1985-1986 with the objective to compensate and ease the load on packing-case wood problem. Poplar being a soft wood species will be complementary to the packing case industry which supplies cases to grape and other horticultural crops cultivations in Western Maharashtra. Cuttings of 12 cultivars (clones) of Populus deltoides, 2 cultivars (clones) of P. x euramericana supplied by the Silviculturist, Southern region, Kanpur, U.P. 4 cultivars each of Populus deltoides of U.S.A. origin, Australian source and 1 cultivar of Populus nigra of Ankara origin, Turkey source supplied by Silviculture Division, F.R.I., Dehra Dun were tried in two nurseries of Forest Department and Directorate of Social Forestry, as well as in private people's plots and farms around Nashik and Pune Districts during February/March 1985. Impressed by the relative success of these trials of poplars carried out earlier, introduction trials were taken up in College of Agriculture, Pune during Feb. 1992 by using Entire Transplants (ETPs) of 5 cultivars of L & S series from Haldwani and Tata Energy Research Institute, Delhi. These are discussed here since the success is impressive. The performance of the above mentioned cultivars are assessed in light of measurements taken in October, 1999.